Analisis Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan Badan Usaha Milik Desa (BUMDes) Desa Jatirejo Lendah Kulon Progo - Fitri Rahmawati; Titin Ekowati (MASMAN Master Manajemen, 2025)
This study aims to analyze the development of Human Resources (HR) and employee performance in improving skills, abilities and behavior so as to improve their performance in carrying out the operations of the Village-Owned Enterprise (BUMDes) of Jatirejo Lendah Kulon Progo Village. The method in this study is a qualitative descriptive method. The data collection techniques used in this study are observation, interviews and documentation. The sample in this study amounted to 7 respondents. While the analysis technique uses a deductive method that analyzes general data to draw specific conclusions. The results of the study indicate that human resource development in improving the performance of BUMDes employees is very important in an organization, Human resources in an organization must have training, knowledge, skills and motivation. Human resource development through education, there are still employees with Junior High School (SMP) education, training has been carried out with Kulon Progo district and D.I. Yogyakarta provincial level, but not all employees participate regularly skills, in general employees have good work skills, although not optimal. Based on the analysis of human resource development to improve employee knowledge, skills and motivation so that they can carry out their duties and responsibilities well.